Class attendance signing system using students' smart card (barcode) / Wan Azlena Wan Mohamad - Wan Mohamad, Wan Azlena (2007)
As the world has moving towards the technology era, all of the universities and industries have started to upgrade their performance using computer and technology. University Technology Mara (UiTM) is one of the universities that are moving towards technology era by implementing the electronic system management to replace the traditional method of UiTM system management. Nowadays, as system management is being delivered through computer, software and application, the usage of barcode are common in system management in universities or industries, in UiTM, the usage of barcode is already implementing in cafe and library system management. Networking has grown tremendously over the past several years all over the world. Networking support structured connection between computers which are found more effective and efficient in managing a system. In UiTM, Fakulti Teknologi Maklumat dan Sains Kuantitatif (FTMSK) has a network: called Local Area Network: (LAN) which provides connection between computers within FTMSK. This project implement client-server network which connects two computers through a cable, one computer works as client and the other works as server.